Malaysia-EU trade relationship and EU foreign direct investment in the Malaysian manufacturing sector - Abdul Karim, Noor Al-Huda (Universiti Utara Malaysia, 2008)
The European Union (EU) is a major trading partner of Malaysia.The EU is the third largest export market for Malaysia after the Association of South East Asian Nations (ASEAN) and the United States ((US).Regarding foreign direct investment (FDI), the EU has been the biggest foreign investor in the manufacturing sector in Malaysia for the past seven years.This paper focuses on the importance of trade in promoting FDI flows from the EU member countries into the manufacturing sector in Malaysia. The FDI panel data cover a period from 1980 to 2005.A log-linear model of trade-EU FDI is selected in which the explanatory variables are total trade and trade openness of the host country.The empirical results from regression suggest that the EU FDI in the manufacturing sector is significantly influenced by Malaysia’s trade with the EU member countries and the level of the host country’s trade openness.Positive relationships between the two variables and the EU FDI indicate that the EU FDI is a complement to Malaysia’s trade.